Housing Industry Transitions: An Urban Living Lab in Melbourne, Australia. Issue 2 (2nd April 2020) - Moore, Trivess; Horne, Ralph; Doyon, Andréanne
ABSTRACT: Urban housing experiments test real-world applications of sustainable, liveable, affordable and innovative developments. However, there is limited evidence of how they influence the wider building regime through the facilitation of new shared experiences, networks and relations. This paper explores the influence of a government-led demonstration project in Melbourne, Australia. Interviews with 14 key industry stakeholders reveal that, while some innovations had limited impact on practice, others resulted in take-up. The case adds to previous studies on the contested nature of sustainable building experiments and develops empirical insights on how such developments shape and are shaped by industry low carbon transitions. 城市住宅实验测试可持续、宜居、可负担和创新发展的现实应用. 然而，通过促进新的共同经验、网络和关系，它们如何影响更广泛的建筑制度的证据有限. 本文探讨了澳大利亚墨尔本政府主导的示范项目的影响. 对14个主要行业利益相关者的采访显示，虽然一些创新对实践的影响有限，但其他创新导致了接受. 该案例补充了以往关于可持续建筑实验的争议性研究，并发展了关于此类发展如何形成以及如何由工业低碳转型形成的经验见解.